Nonmuscle-Invasive Bladder Cancer: What's Changing and What has Changed. Issue 1 (February 2017) - Manikandan, Ramanitharan; Rodriguez, Oscar; Parada, Rubén; Palou Redorta, Joan
Purpose: Nonmuscle-invasive bladder cancer (NMIBC) is a challenging disease to manage primarily due to its varied clinical course. The management of NMIBC has witnessed a widespread change with respect to its diagnosis and treatment. Although transurethral resection (TUR) and adjuvant bacillus Calmette–Guerin (BCG) stills remain the cornerstone, newer protocols has come into vogue to achieve optimal care. On the basis of a literature review, we aimed to establish 'what changes has already occurred and what is expected in the future' in NMIBC. Methods: A Medline search was performed to identify the published literature with respect to diagnosis, treatment and future perspectives on NMIBC. Particular emphasis was directed to determinants such as the quality of TUR and the newer modifications, Re-TUR, current status of newer macroscopic and microscopic imaging, role of urinary biomarkers, clinical, histologic and molecular predictors of high-risk disease, administration of intravesical agents, salvage therapy in BCG recurrence and the current best practice guidelines were analyzed. Results and Conclusions: Optimal TUR, restaging in select group, incorporation of newer endoscopic imaging and judicious administration of intravesical chemo-immunotherapeutic agents can contribute to better patient care. Although there is a plethora of urinary markers, there is insufficient evidence for their use in isolation. The future probably lies in identification of genetic markers to determine disease recurrence, nonresponders to standard treatment and early institution of alternative/targeted therapy.